PENGARUH PENERAPAN STRATEGI PEMBELAJARAN AKTIF TIPE COLLEGE BALL TERHADAP PEMAHAMAN KONSEP MATEMATIS SISWA KELAS VIII SMPN 35 PADANG - Halomoan, Arisman; K, Delsi; Yunita, Alfi (STKIP PGRI Sumbar, 2013)
The problems find is by the studentâs understanding of mathematical concepts SMPN 35 Padang is low. This research aims to determine: 1) how the study activity of studentâs by applying a strategy College Ball to the studentâs understanding mathematical concepts in class VIII SMPN 35 Padang, 2) whether the studentâs understanding of mathematical concepts by applying active learningÂ strategies College Ball type is better than the studentâs understanding of mathematical concepts that apply to conventional teaching in class VIII SMPN 35 Padang. This type of research is experimental. Population of this research is student`s at grade VIIIÂ SMPN 35 Padang. Technique of random sampling, VIII1 as experimental class and VIII2 as control class. Research instrument is the observation sheet students learning activities and the ultimate test with the reliabilitation of 0,94. Results of hypothesis testing with the -test it obtained, Â = 2,82 and .= 0,17, obtained Â â¥ . This means the hypothesis is accepted at the level of 95%. In conclusion, the studentâs understanding of mathematical concepts by applying active learning strategies College Ball type is better than the studentâs understanding of mathematical concepts that apply conventional teaching in class VIII SMPN 35 Padang